The Effect of Capital Market Career Socialization and Financial Management Knowledge on Accounting Students' Interests in Capital Market Careers - Silviana Luqman; Tetty Lasniroha; Achmad Fadjar; R. Wedi Rusmawan; Veronica Veronica; Gedizza Gedizza; Zakiah Zakiah (The International Journal of Business Review (The Jobs Review), 2022)
The purpose of the study was to find out whether students were interested in a career in the capital market after socialization and obtaining knowledge of financial management. The research used survey method. Collecting data by distributing questionnaires through google meet to 104 respondents. Respondents consisted of undergraduate accounting students, PPAk and MAKSI. Data analysis using multiple linear regression, data processing using SPSS v.25 software. The results showed that the socialization of capital market careers did not affect students' interest in a career in the capital market, but knowledge of financial management did affect students' interest in a career in the capital market. The research findings show that there are more PPAk and MAKSI students respondents than undergraduate students, it is suspected that the cause of socialization has no effect on interest, because the majority of PPAk and MAKSI respondents are already working. It is recommended that further researchers choose research respondents for final year undergraduate accounting students or have just graduated from undergraduate accounting but have not worked.